PENGANTAR KE FILSAFAT HIKMAH (`IRFÂN) ALLAMAH SAYYID MUHAMMAD HUSAIN THABTHABÂI - salahuddin harahap (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2019)
Allamah Muhammad Husain al-Thabthabani succeeded in initiating the revival of philosophical thought in Iran and Qum after almost dimming after the death of Mulla Sadra. Although there are not many things that are truly new from his thoughts on Mulla Sadra Philosophy, it can be said that in his hands a number of Mulla Shadra's ideas which are considered complicated can be described quite well so that they are easy to understand. His thoughts on philosophy were at least contained in two of his very famous works, namely Bidâyatu al-Hikmah and Nihâyatu al-Hikmah which at the same time strengthened his position as the leading Philosophy after Mulla Sadra. That is why it is deemed necessary to discuss the thoughts of Allamah Muhammad Husayn al-Thabthabi's Philosophy.Keywords: `irfân, Allamah Sayyid Muhammad Husain Thabthabâi.